2019
DOI: 10.2478/adms-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slide Burnishing on the Surface Layer and Fatigue Life of Titanium Alloy Parts

Abstract: The paper presents the results of a study investigating the effect of slide burnishing on the surface roughness, surface layer microhardness and fatigue life of Ti6Al2Mo2Cr titanium alloy parts. The burnishing process was performed with the use of a diamond tip tool. Different machining fluids were used as machining media. Prior to burnishing, the samples were subjected to turning. The burnishing process led to reduced surface roughness (average roughness Ra decreased by 3.5 times and roughness Rz decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
(30 reference statements)
0
11
0
1
Order By: Relevance
“…For evaluation of measured hardness value improvements by burnishing, improvement ratios were introduced, which are shown in Eq. ( 2) [15]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluation of measured hardness value improvements by burnishing, improvement ratios were introduced, which are shown in Eq. ( 2) [15]:…”
Section: Resultsmentioning
confidence: 99%
“…Burnishing studies of wrought titanium alloys showed that beyond machining parameters also lubricants may have significant effect to surface hardness, wear resistance and fatigue [15,16], roller burnishing experiments of Ti4Al4V show that significant improvement of surface roughness and hardness can be achieved even in cryogenic conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nagniatanie ślizgowe powoduje powstanie głębokiej warstwy utwardzonej w której wywołany zostaje stan naprężeń ściskających [3]. Ze względu na mały promień narzędzia nagniatanie ślizgowe charakteryzuje się występowaniem niewielkich sił, co umożliwia obróbkę części o małej sztywności [4]. Proces nagniatania pozwala na osiągnięcie takich korzyści jak [5]: wzrost twardości powierzchni, wzrost odporności zmęczeniowej, możliwość obróbki powierzchni o dużym promieniu naroża, możliwość obróbki powierzchni o małej wartości współczynnika tarcia, zdolność do wytworzenia wysokiej gładkości powierzchni, minimalne nagrzewanie się warstwy wierzchniej podczas obróbki, możliwość stosowania narzędzi dogniatających zamocowanych na tokarkach uniwersalnych, wysoką wydajność procesu, niskie zużycie energii procesu nagniatania.…”
Section: Wprowadzenieunclassified
“…They have shown a significant impact on the fretting fatigue crack propagation lifetime. Zaleski and Skoczylas [18] investigated experimentally the effects of slide burnishing on the surface roughness, surface layer microhardness, and fatigue life of Ti6Al2Mo2Cr titanium alloy parts, who found that the changes in the surface layer properties induced by slide burnishing lead to an increased lifetime of the components. Based on the above, it can be noted that the fretting is a challenging physical phenomenon, which involves different sciences, i.e.…”
Section: Introductionmentioning
confidence: 99%